Acceptance of Novel Perimetry Methods in Germany: Virtual Reality Perimetry and Tablet-based Perimetry in Glaucoma Patients - Schrittenlocher, Silvia; Lüke, Vincent; Irle, Hanne; Weliwitage, Jithmi; Lüke, Jan Niklas; Kong, George; Vingrys, Algis J.; Lappas, Alexandra; Cursiefen, Claus; Dietlein, Thomas S. (Klinische Monatsblätter für Augenheilkunde, 2025)
Purpose The aim of this study was to investigate the acceptance of innovative perimetry methods such as virtual reality perimetry (VRP) and tablet-based perimetry (TBP) in comparison to conventional hemisphere perimetry (HP) in glaucoma patients for the first time in Germany.Patients and Methods We examined 204 glaucoma patients using the 30 – 2 TOP algorithm (Octopus, Haag-Streit) followed by one of the two new methods: Group 1 (VRP; n = 101) and Group 2 (TBP using the Melbourne Rapid Fields Glaucoma App; n = 103). Subsequently, patients were asked to fill out a questionnaire on their experience with the new examination compared to the conventional examination.Results More than three-quarters of patients at 77% in Group 1 (VR) and 89.9% of patients in Group 2 (TBP) found the respective new examination method “easier” or “much easier” than the conventional HP. An overwhelming majority of patients in Group 1 and Group 2 found the new method more comfortable at 86% and 90.9%, respectively. Examination durations were: 2.67 ± 0.98 min for HP, 6.26 ± 1.88 min for VR perimetry, and 4 ± 0.71 min for the tablet method; figures given as means ± standard deviation. Just over half the patients at 51% found HP and VR headset to be similar for duration with 54% preferring the tablet over conventional hemisphere perimetry. By far the most patients in Groups 1 and 2 at 80% and 81.8%, respectively, reported willingness to use the new perimetry method regularly in future follow-up examinations.Conclusion Most glaucoma patients surveyed consistently responded favourably to VR headset and tablet-based perimetry, preferring these examinations to conventional hemispherical perimetry.Hintergrund Ziel dieser Studie war es, erstmalig in Deutschland die Akzeptanz von innovativen Perimetriemethoden, wie die Virtual-Reality-Brillen-Perimetrie (VRP) und die Tablet-basierte Perimetrie (TBP) im Vergleich zur konventionellen Halbkugelperimetrie (HKP) bei Glaukompatienten zu untersuchen.Patienten und Methoden 204 Glaukompatienten wurden mit dem Programm 30 – 2 TOP (Octopus, Haag-Streit) untersucht und anschließend mit einer der beiden neuen Methoden: Gruppe 1 (VRP; n = 101) und Gruppe 2 (TBP mittels der Melbourne Rapid Fields Glaucoma App; n = 103). Anschließend wurde einfragebogen über die Erfahrung mit der neuen Untersuchung im Vergleich zur konventionellen Untersuchung ausgefüllt.Ergebnisse 77% der Patienten aus Gruppe 1 (VRP) und 89,9% der Patienten aus Gruppe 2 (TBP) beurteilten die Untersuchung mit der jeweiligen neuen Untersuchungsmethode als „einfacher“ oder „viel einfacher“ im Vergleich zur konventionellen HKP. Hinsichtlich der Bequemlichkeit gaben 86% bzw. 90,9% der Patienten der Gruppe 1 bzw. Gruppe 2 an, die jeweils neue Methode zu bevorzugen. Die Dauer der Untersuchung betrug mit der HKP 2,67 ± 0,98 min (Mittelwert ± Standardabweichung), mit der VR-Brille 6,26 ± 1,88 min (Mittelwert ± Standardabweichung) und mit dem Tablet bei 4 ± 0,71 min (Mittelwert ± Standardabweichung). Bezogen auf diesem Aspekt fand die Mehrheit der Patienten beide Untersuchungen (HKP und VRP) zu 51% gleich und beim Vergleich zum Tablet bevorzugte die Mehrheit zu 54% das Tablet gegenüber der HKP. 80% bzw. 81,8% der Patienten aus Gruppe 1 bzw. 2 konnten sich vorstellen, jeweils die neue Perimetriemethode regelmäßig als Verlaufskontrolle zu verwenden.Schlussfolgerung Die Mehrheit der befragten Glaukompatienten empfand die Untersuchung mit der Virtual-Reality-Brillen-Perimetrie und der Tablet-basierten Perimetrie durchweg als positiv und bevorzugte diese gegenüber der konventionellen Halbkugelperimetrie.
Keywords: visual field; glaucoma; virtual reality perimetry; Melbourne Rapid Field; tablet perimetry